Attribute preferences, participation intention and economic value of carbon offset programme for airline passengers in Malaysia - Shaari, Nur Fatihah (2019)
Air transportation is one of the fastest growing in terms of demand. People prefer to board a plane for travelling due to several factors including the airfares which are affordable for people from all walks of life. Although carbon dioxide (CO2) emissions from air transportation only contribute 4% (which equals to nearly 781 million tonnes of carbon dioxide (CO2) for every flight) of total pollution, it is one of the fastest growing sources of greenhouse gas emissions (GHG). In order to reduce CO2 emissions, there are various alternatives that have been adopted by airlines including the use of sophisticated technologies for operation (less carbon emissions), and the implementation of carbon offset programme. This programme helps in reducing the carbon emissions, by offsetting the emissions released to benefit “green initiatives” such as through renewable energy projects, energy efficiency and forest management projects. This study aims to assess attribute preferences, participation intention and economic value of carbon offset programme for airline passengers in Malaysia. This study employed the Contingent Valuation Method (CVM), Choice Experiment (CE) method, and Partial Least Squares Structural Equation Modelling (PLS-SEM) method. A total of 823 passengers for CVM and CE method, and 403 passengers for PLS-SEM method were selected from Kuala Lumpur International Airport (KLIA) and Kuala Lumpur International Airport 2 (KLIA2) as respondents for this study. The CVM derived the appropriate Malaysian flight airfare for better environmental performance. The Logit model was defined by using the dichotomous double-bounded method to elicit the value that is appropriate for the airfare from price bid. The outcomes of the study showed that as the price bid increased, the probability of saying “yes” decreased. Educated passengers with higher income agreed to pay extra for their airfare to support environmental initiatives. The estimated mean for willingness to pay among passengers with regards to the appropriate airfare towards carbon offset programme was RM80.44, which the value is a guideline to charge as an additional charge on top of the original airfare. By using CE method, the attributes identified for carbon offset programme were CO2 emission, type of project, project location and voluntary payment. The Conditional Logit and Mixed Logit model were applied to estimate the marginal value of the attributes and the attributes that were most preferred. The results showed passengers chose forest management as the most important attribute for carbon offset programme and the marginal value for this attribute was RM84.82, in which it is based on the best model selected (Mixed Logit model with interaction). The New Ecological Paradigm scale, the Theory of Planned Behaviour and variables from past literature were used to measure general environmental attitudes, intermediate beliefs, and specific behaviour attitudes and norms. The PLS-SEM method was used to investigate the factors influencing Malaysian passengers towards carbon offsets. The results showed that only general environmental attitudes and specific environmental attitude had a direct relationship with intentions. While testing for an indirect relationship, it was revealed that the general environmental attitude did not have an indirect relationship with intention, as it was mediated by intermediate beliefs and specific attitude. The findings of this study provide policy recommendation to policymakers, airlines and passengers of an alternative to reduce the CO2 emissions. By having information regarding the appropriate airfare, it will help the airline to impose a reasonable fee on top of their airfare in support of environmental concerns. In addition, this study can encourage the airlines management, government and other related parties to take drastic action by implementing the carbon offset programme in Malaysia based on the selected attribute that passengers preferred which is forest management. The information obtained in terms of monetary value will help to convince Malaysian airlines to implement the carbon offset program accordingly. This study is expected to motivate people to contribute money in realising this programme and to support the country’s effort in moving towards becoming a low-carbon economy.